Effects of Probiotics on Intestinal Mucosa Barrier in Patients With Colorectal Cancer after Operation: Meta-Analysis of Randomized Controlled Trials. Issue 15 (April 2016) - Liu, Dun; Jiang, Xiao-Ying; Zhou, Lan-Shu; Song, Ji-Hong; Zhang, Xuan
Abstract : Abstract: Many studies have found that probiotics or synbiotics can be used in patients with diarrhea or inflammatory bowel disease for the prevention and treatment of some pathologies by improving gastrointestinal barrier function. However, there are few studies availing the use of probiotics in patients with colorectal cancer. To lay the foundation for the study of nutritional support in colorectal cancer patients, a meta-analysis has been carried out to assess the efficacy of probiotics on the intestinal mucosa barrier in patients with colorectal cancer after operation. To estimate the efficacy of probiotics on the intestinal mucosa barrier in patients with colorectal cancer after operation, a meta-analysis of randomized controlled trials has been conducted. Databases including PubMed, Ovid, Embase, the Cochrane Central Register of Controlled Trials, and the China National Knowledge Infrastructure have been searched to identify suitable studies. Stata 12.0 was used for statistical analysis, and sensitivity analysis was also conducted. Six indicators were chosen to evaluate probiotics in protecting the intestinal mucosa barrier in patients with colorectal cancer. Ratios of lactulose to mannitol (L/M) and Bifidobacterium to Escherichia (B/E), occludin, bacterial translocation, and levels of secretory immunoglobulin A (SIgA), interleukin-6 (IL-6), and C-reactive protein (CRP) were chosen to evaluate probiotics in protecting the intestinal mucosa barrier in patients with colorectal cancer. Seventeen studies including 1242 patients were selected for meta-analysis, including 5 English studies and 12 Chinese studies. Significant effects were found in ratios of L/M (standardized mean difference = 3.83, P = 0.001) and B/E (standardized mean difference = 3.91, P = 0.000), occludin (standardized mean difference = 4.74, P = 0.000), bacterial translocation (standardized mean difference = 3.12, P = 0.002), and levels of SIgA (standardized mean difference = 2.91, P = 0.004) and CRP (standardized mean difference = 4.21, P = 0.000), but no significant effects were found for levels of IL-6 (standardized mean difference = 1.33, P = 0.184). Probiotics can effectively protect the intestinal mucosa physical and biological barrier in patients with colorectal cancer after operation. However, to evaluate the protective effect on intestinal mucosal barrier, further studies on the type and concentration of the probiotics, duration of therapy, and the therapeutic route are required.